Value of Shear Wave Elastography Versus Contrast‐Enhanced Sonography for Differentiating Benign and Malignant Superficial Lymphadenopathy Unexplained by Conventional Sonography. (30th November 2016) - Tan, Shi; Miao, Li‐Ying; Cui, Li‐Gang; Sun, Peng‐Fei; Qian, Lin‐Xue
Abstract : Objectives: This study aimed to compare the efficacy of shear wave elastography (SWE) and contrast‐enhanced sonography in the differential diagnosis of superficial lymphadenopathy with abnormal imaging findings, which could not be otherwise confirmed by conventional sonography. Methods: Forty‐two enlarged superficial lymph nodes in 42 patients who met the screening criteria for this study were evaluated by both contrast‐enhanced sonography and SWE. All lymph nodes underwent both methods using biopsy pathologic findings as a reference standard. Results: The maximum elastic modulus, mean elastic modulus, and standard deviation of the elastic modulus were the main distinguishing features on SWE; they were significantly higher in malignant lesions than benign ones. The threshold value for the maximum elastic modulus was set at 37.9 kPa, and the sensitivity, specificity, and accuracy of differential diagnosis of superficial lymph nodes were 81.8%, 80.0%, and 81.0%, respectively. The diagnosis of benignity and malignancy by this index was statistically significant ( P  < .001). The lymph nodes were divided into benign and malignant groups according to different types based on the degree and range of intensity on contrast‐enhanced sonography: intense or moderate homogeneous enhancement (n = 26) and heterogeneous, low homogeneous, or absent enhancement (n = 16). The sensitivity, specificity, and accuracy of contrast‐enhanced sonography were 27.3%, 50.0%, and 38.1%. There was no statistically significant difference in the values between the benign and malignant groups (χ 2  = 2.295; P  = .130). Conclusions: Compared with contrast‐enhanced sonography, SWE has better diagnostic value and efficiency in differentiation of superficial lymph nodes unexplained by conventional sonography. When conventional sonography cannot differentiate malignant superficial lymph nodes from benign ones, SWE is a useful adjunctive tool for assessment of lymph nodes.